The influence of antenatal imaging on prenatal bonding in uncomplicated pregnancies: a mixed methods analysis - Emily Skelton; Daniel Cromb; Alison Smith; Gill Harrison; Mary Rutherford; Christina Malamateniou; Susan Ayers (BMC, 2024)
Abstract Background Prenatal bonding describes the emotional connection expectant parents form to their unborn child. Research acknowledges the association between antenatal imaging and enhanced bonding, but the influencing factors are not well understood, particularly for fathers or when using advanced techniques like fetal magnetic resonance imaging (MRI). This study aimed to identify variables which may predict increased bonding after imaging. Methods First-time expectant parents (mothers = 58, fathers = 18) completed a two-part questionnaire (QualtricsXM™) about their expectations and experiences of ultrasound (n = 64) or fetal MRI (n = 12) scans in uncomplicated pregnancies. A modified version of the Prenatal Attachment Inventory (PAI) was used to measure bonding. Qualitative data were collected through open-ended questions. Multivariate linear regression models were used to identify significant parent and imaging predictors for bonding. Qualitative content analysis of free-text responses was conducted to further understand the predictors' influences. Results Bonding scores were significantly increased after imaging for mothers and fathers (p < 0.05). MRI-parents reported significantly higher bonding than ultrasound-parents (p = 0.02). In the first regression model of parent factors (adjusted R 2 = 0.17, F = 2.88, p < 0.01), employment status (β = -0.38, p < 0.05) was a significant predictor for bonding post-imaging. The second model of imaging factors (adjusted R 2 = 0.19, F = 3.85, p < 0.01) showed imaging modality (β = -0.53), imaging experience (β = 0.42) and parental excitement after the scan (β = 0.29) were significantly (p < 0.05) associated with increased bonding. Seventeen coded themes were generated from the qualitative content analysis, describing how scans offered reassurance about fetal wellbeing and the opportunity to connect with the baby through quality interactions with imaging professionals. A positive scan experience helped parents to feel excited about parenthood. Fetal MRI was considered a superior modality to ultrasound. Conclusions Antenatal imaging provides reassurance of fetal development which affirms parents' emotional investment in the pregnancy and supports the growing connection. Imaging professionals are uniquely positioned to provide parent-centred experiences which may enhance parental excitement and facilitate bonding.